PENGEMBANGAN MEDIA PAPAN CATUR PERKALIAN PADA MATA PELAJARAN MATEMATIKA SISWA KELAS II SEKOLAH DASAR - Lika Apreasta; Yulia Darniyanti; Lidya Monalisa (STKIP Subang, 2024)
The aim of this research is to develop multiplication chessboard media in mathematics subjects, multiplication material, in order to add to the existing media in schools and produce the development of multiplication chessboard media for class II elementary schools that is valid, practical and effective so that it can improve student learning outcomes at SDN 11 Sitiung. This type of research is research and development (Research and Development, R & D) with a 4-D development model which includes Define, Design, Develop and Disseminate. This research was carried out at SDN 11 Sitiung. The data analysis technique used in the research is descriptive data analysis, namely describing the level of validity, practicality and effectiveness. The results of the research show that the development of the multiplication chess board for mathematics subjects has reached very valid criteria with a percentage of 75.00%. Then, the results of the questionnaire responses from students and teachers obtained an average percentage of 88.33%, which shows that the multiplication chess board media in mathematics subjects in class II elementary schools has met the very practical criteria. Meanwhile, the results of the effectiveness test were in the form of test questions filled in by students and obtained a percentage of 89.47% in the very effective category.